System Dynamics and Statistical Modeling of Severe Storms: The Case of Charlottetown, P.E.I., Canada - Beigzadeh, Shima (Université d'Ottawa / University of Ottawa, 2014)
Scientific evidence points to a changing global climate. The most vital and visible impacts of this phenomenon for sea-level communities are sea-level rise, coastal erosion, and more frequent severe coastal storms. However, limited research has been conducted to date to project the damage from rising maximum water levels and corresponding storm surges, and their impacts on the sustainability of coastal communities. This research focuses on the urban coastal community of Charlottetown, Prince Edward Island (P.E.I.), Canada as part of the C-Change International Community University research Alliance (ICURA), “Managing Adaptation to Environmental Change in Coastal Communities: Canada and the Caribbean.” The stochastic process that underlies, maximum observed water levels in Charlottetown, is modeled using historical data. Maximum observed water levels and storm surges are represented by fitted conditional and marginal univariate probability density functions. The statistical package “Easy-Fit” is used as a tool for analyzing goodness of fit to the historical data for maximum observed water levels in Charlottetown. A System Dynamics (SD) model, using STELLA, is developed to simulate the projected impacts of maximum observed water levels on the City of Charlottetown. The SD model captures the dynamics of the four pillars of community sustainability, namely Environmental, Economic, Social-Cultural and Human sectors identified for the City of Charlottetown. The model defines and evaluates the robustness of alternative adaptation strategies for various model scenarios to projected storms over a long-term planning period. The results quantify the vulnerability of Charlottetown. The analysis of the results from implementing 3 main adaptation strategies for protection, accommodation, and retreat scenarios as well as the ones from the most common current response of “doing nothing”, provide information on the dynamic and pillar-related impacts of storms on Charlottetown. Analysis of these strategy options clearly indicates that doing nothing in the face of more frequent severe storms is an inefficient strategy. Model results show that the protect strategy is unlikely to deliver complete protection, and the retreat option is costly and not well received. The accommodation strategy including a combination of protection options and controlled retreat will provide the most robust option for the coastal City of Charlottetown. The SD model and analysis provides a framework for the evaluation of adaptation strategies for alternative coastal communities.
Keywords: Maximum Observed Water Level; Sea level rise; System Dynamics using STELLA; Coastal community; Adaptive Capacity; Charlottetown